2000
DOI: 10.1536/jhj.41.385
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis of Peripheral Blood Lymphocytes is Induced by Catecholamines.

Abstract: We explored the mechanism through which patients sometimes show immunosuppression after cardiac surgery. To test the hypothesis that commonly used drugs could cause apoptosis of immune cells, the proapoptotic effects of heparin and catecholamines (dopamine and dobutamine) on peripheral blood lymphocytes were evaluated. Peripheral blood lymphocytes were purified from blood samples of normal healthy volunteers. These cells were cultured in the presence of heparin, dobutamine or dopamine. The apoptosis was quanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
10
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(12 citation statements)
references
References 35 publications
2
10
0
Order By: Relevance
“…Also, in accordance with previous studies [ 20 , 25 ], our results indicate a slight reduction in the percentage of apoptotic cells in simulated microgravity alone, although this effect could not be regarded as statistically significant. Furthermore, as published before [ 67 ], we also found that isoproterenol inhibited radiation (2 Gy)-induced apoptosis in cells incubated in 1 g (Iso × R (1 g )) although this was not the case in µg. Isoproterenol-mediated inhibition of radiation-induced apoptosis could be due to an increase in cAMP signaling, which has been shown to inhibit apoptosis by reducing ATM-dependent activation of NF-κB [ 68 ] and by preventing p53 accumulation [ 34 ].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Also, in accordance with previous studies [ 20 , 25 ], our results indicate a slight reduction in the percentage of apoptotic cells in simulated microgravity alone, although this effect could not be regarded as statistically significant. Furthermore, as published before [ 67 ], we also found that isoproterenol inhibited radiation (2 Gy)-induced apoptosis in cells incubated in 1 g (Iso × R (1 g )) although this was not the case in µg. Isoproterenol-mediated inhibition of radiation-induced apoptosis could be due to an increase in cAMP signaling, which has been shown to inhibit apoptosis by reducing ATM-dependent activation of NF-κB [ 68 ] and by preventing p53 accumulation [ 34 ].…”
Section: Discussionsupporting
confidence: 82%
“…However, without radiation isoproterenol induces apoptosis in 1 g but not in µg leading to a significant interaction between response to isoproterenol and microgravity (Iso × g). It has been shown that stimulation of β-adrenergic receptor induces apoptosis in thymocytes [ 33 ] and the catecholamine dopamine and dobutamine induce apoptosis in peripheral blood mononuclear cells after 24 and 48 h of ex vivo incubation [ 67 ]. The lack of isoproterenol-mediated inhibition of apoptosis in µg could simply reflect the fact of lower apoptotic cells in microgravity.…”
Section: Discussionmentioning
confidence: 99%
“…Differences in baseline characteristics in the present study could not explain differences in outcomes, since they were minor and for the most part not involving variables shown in previous large studies to confer risk in AHF. Previous studies hypothesized that the low relative lymphocyte count reflects activation of the hypothalamic-pituitary-adrenal axis [14,15,16,17]. As mentioned above, the importance of cortisol in this respect is emphasized by the relationship between both cortisol levels and relative lymphopenia and the fact that cortisol elevations are commonly seen in acute stress responses.…”
Section: Discussionmentioning
confidence: 97%
“…ACTH, corticosteroids, catecholamines, cytokines, chemokines and allarmines play an important role in the initiation and maintenance of the inflammatory response to injury, and also in the regulation of the albumin gene expression [8]. The complex network of cytokines appears to be disrupted, especially after surgery [20]. Interleukin-1β, -6, -8 and TNF-α, some suppressive cytokines such as Interleukin-10, -4 and Interleukin-1 receptor antagonist significantly increase just after the beginning of surgery, while Interferon-γ and Interleukin-2 are markedly reduced [20].…”
Section: Discussionmentioning
confidence: 99%
“…The complex network of cytokines appears to be disrupted, especially after surgery [20]. Interleukin-1β, -6, -8 and TNF-α, some suppressive cytokines such as Interleukin-10, -4 and Interleukin-1 receptor antagonist significantly increase just after the beginning of surgery, while Interferon-γ and Interleukin-2 are markedly reduced [20]. This imbalance alters the immune response and may in part explain the correlation between low levels of lymphocytes and length of stay found in surgery ward I.…”
Section: Discussionmentioning
confidence: 99%